Regional Innovation Impact of Universities - Tijssen, Robert (Edward Elgar Publishing, 2021)
Driven by European Union policy challenges, this cutting-edge book focuses upon the Regional Innovation Impact (RII) of universities, to analyse the socioeconomic impact that universities in Europe have on their hometowns, metropolitan areas and regions.